E Efektivitas Kartu Kredit Pemerintah Untuk Pembayaran Belanja Perjadin Ombudsman RI: indonesia - Pupung Bagus Kuncoro; Ardiansyah (JAKTABANGUN: Jurnal Akuntansi & Pembangunan, 2024)
The Government Credit Card (KKP) has been designated as a method for paying bills from government partners starting in July 2019 by the Government of the Republic of Indonesia. This is regulated in the Regulation of the Minister of Finance of the Republic of Indonesia number 196/PMK.05/2018 concerning Procedures for Payment and Use of Government Credit Cards ( Sistem et al., n.t.) . The Ombudsman of the Republic of Indonesia, as one of the State Institutions that has the authority to supervise the implementation of public services in Indonesia, often makes official trips within and outside the country. This is an encouragement for the Indonesian Ombudsman to maximize the use of KKP as a method of paying for official travel expenses. The purpose of writing this scientific work is to determine the level of effectiveness of using KKP as a payment method for official travel expenses at the Indonesian Ombudsman. Researchers used a qualitative approach with a case study research design. The research was conducted at the Ombudsman of the Republic of Indonesia. Researchers used documentation and interviews as data collection methods. Participants involved consist of Commitment Making Officials, Expenditure Treasurers, KKP administrators, KKP holders and official travelers.